2015
DOI: 10.2299/jsp.19.147
|View full text |Cite
|
Sign up to set email alerts
|

Ball Trajectory Extraction in Team Sports Videos by Focusing on Ball Holder Candidates for a Play Search and 3D Virtual Display System

Abstract: When team sports coaches instruct their team members, a sample video is needed for an offensive instruction. However, it is very difficult to search a video for the parts of interest, and it takes a long time to compile a database, for example, ball trajectories and player locations, because sports videos have many periods with no play such as timeouts. In particular, information on the ball trajectory is very important for tactical analysis. However, it is currently inputted manually, which is time-consuming.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The methods used for their tracking are applied in various fields, including the army, industry, medicine, and robotics [22]. It is very difficult to track moving objects in real time, e.g., a ball in sports games [21,[23][24][25][26]. However, at present, this problem is an important component of sports analysis because the information about the position of the ball and its velocity may be obtained [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for their tracking are applied in various fields, including the army, industry, medicine, and robotics [22]. It is very difficult to track moving objects in real time, e.g., a ball in sports games [21,[23][24][25][26]. However, at present, this problem is an important component of sports analysis because the information about the position of the ball and its velocity may be obtained [26].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested an innovative approach to the subject by defining tracking in terms of deciding which player is in possession of the ball at any given time. Kurano et al [25] described a method of automatic ball trajectory extraction in American football. They focused on ball holder prediction and constructed a play search and 3D virtual display system using information concerning the ball trajectory and the Unity development environment.…”
Section: Introductionmentioning
confidence: 99%